Gassman transmediale: Il Mattatore del miracolo tra teatro, cinema e tv - Bertolotti, Agnese (Mediascapes journal, 2019)
The aim of this essay is to evaluate and validate the role of Vittorio Gassman as a transmedial continuum in the media industry during the Italian second post-war years. In the 1950s a new evolved and complex media system emerged; the reason of this evolution has to be found not only in the country's economic growth, but is also a consequence of the birth of Italian television in 1954, which constituted the most significant change in the cultural consumption of that time. The economic growth of the post war period led to a renewal and expansion of the activities of many of the cultural industries already present in the National territory, and led to the introduction of modern and popular cultural forms, such as the diffusion of illustrated magazines and the birth of a television audience, while the cinema audience was achieving his highest peak in 1955. The television of the early years was considered an indispensable vehicle for culture and entertainment spreading in Italian homes, often triggering forms of intermediation, drawing contents and forms of entertainment directly from the theater. By widely borrowing from the theater texts, contents, directors and actors, the early Italian television seems far from the film industry. For its part, the cinema, fulfilling its role of public diary in perceiving and representing the Italian society, is not indifferent to the new television medium but it uses it by quoting it, showing it and telling it in a quite osmotic process. Vittorio Gassman, already known as theater actor, easily fits into this complex context thanks to the television show Il mattatore. Il Mattatore was a successful tv show aired in 1959 on the only Rai Channel. The program was brilliant and particularly innovative in the format, so much to escape a precise classification and to be defined as a “mixed show”, because of its plurarity of genres, tones and interpretations. The following year, the success of the broadcast will led to the production of a film named after it, directed by Dino Risi and buildt around Vittorio Gassman’s skills. Thanks to the success of the Mattatore_formula, the actor seems to travel between the different media, so Gassman can be defined a pioneer of narrative transmediality, the prototype of transmedia continuum in the theater-cinema-TV system of the Italian economic boom. An analysis of the television show Il Mattatore is therefore proposed, using the definition of transmediality presented by Herny Jenkins in 2006 in his work Convergence Culture, applying the categories that identify the seven cardinal principles of the trans-media narrations in order to validate the figure of Vittorio Gassman-mattatore as a trans-media prototype, which is not just a simple auroral cross-media example extended to the various media